Integrative analysis of transcriptomics and metabolomics reveals the protective effect and mechanism of salidroside on testicular ischemia-reperfusion injury - Jiang, Ya Ping; Liu, Bao Gui; Dang, Yi; Liu, Lin Jie; Pang, Yang; Bai, Xiao Dong; Sun, Feng; Kang, Tian Hong; Zhao, Zheng Hang (Frontiers in Pharmacology, 2024)
Testicular torsion is an urgent urologic disease. After testicular torsion, testicular detorsion surgery is still the golden method to reverse the testicular-torsion condition, and the surgical treatment is irreplaceable. However, surgical treatment is equivalent to a process of blood reperfusion, and no specific drug is available to treat the blood reperfusion injury. Salidroside (SAL) is one of the main effective substances in rhodiola, which has antioxidant and antiapoptosis activities. This study was designed to determine whether SAL exerted a protective effect on testicular I/R injury. In this study, I/R injury model of testis and OGD/R model were used for verification, and SAL was given 100 mg/kg and 0.05mmol/L respectively. After the experiment, Testis tissues and TM4 sertoli cells were collected for histopathic and biochemical analysis. The results revealed that SAL can improve the structure of testicular tissue and regulate the oxidation-antioxidation system. To further understand the molecular mechanism of SAL in treating testicular I/R injury, we integrated the analysis of transcriptomics and metabonomics. Results showed that the Nfr2/HO-1/GPX4/ferroptosis signaling pathway was significantly enriched, indicating that it may be the main regulatory pathway for SAL to treat testicular I/R injury. Then, by transfection with Nrf2 plasmid-liposome, we reversely verified that the Nfr2/HO-1/GPX4/ferroptosis signaling pathway was the main pathway of SAL anti-testicular I/R injury.In conclusion, this study suggested that SAL can protect testicular I/R injury by regulating the Nfr2/HO-1/GPX4 signaling pathway to inhibit ferroptosis, and that SAL may be a potential drug for the treatment of testicular I/R injury.